PERANCANGAN TALENT ACQUISITION DAN ONBOARDING PADA INDUSTRI MAKANAN DAN MINUMAN - Lilis Lilis; Alden Nelson; Novia Clarissa; Helen Salwa; Eriva Riesquita (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research explores the urgency of talent acquisition and onboarding in the food and beverage industry in the era of globalization and technology. The success of this industry relies on effective talent recruitment strategies to maintain competitiveness. The focus involves identifying individuals with technical skills. Onboarding is necessary for the swift integration of new employees with a deep understanding of the industry, food safety, and skill training. This strategy encompasses technical aspects, cultural values of the company, and adaptability to market changes. Using a descriptive analytical and qualitative approach, the study finds that this strategy not only supports short-term growth but also plays a key role in sustaining long-term competitiveness. The article provides practical insights for companies to design and implement effective talent acquisition and onboarding processes in this industry.